2005
DOI: 10.1177/001979390505900108
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prevailing Wage Requirements on the Cost of Low-Income Housing

Abstract: Recent California legislation extends the application of prevailing wage regulations to construction workers building subsidized low-income residential projects. Econometric evidence based on micro data covering 205 residential projects subsidized by the California Low Income Housing Tax Credit since 1996 and completed by mid-2002 demonstrates that construction costs increased substantially under prevailing wage requirements. Estimates of additional construction costs in the authors' most extensive models rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…Almost all of the grantees and two‐thirds of the subgrantees reported that overall, Davis‐Bacon lead to wage and other cost increases (see Table ). These findings are in line with other research conducted over many years on the cost implications of Davis‐Bacon (e.g., Bilginsoy & Phillips, ; Dunn, Quigley, & Rosenthal, ; Fraundorf, Farrell, & Mason, ; Vincent & Monkkonen, ) though some studies have found to cost impacts (e.g., Duncan, ). Discussions with over a dozen subgrantees held during case study visits suggest that DoL adopted most of the wage rates that the subgrantees were already paying their in‐house staff but that wage rates for specialty jobs, such as for electricians working in multifamily buildings five floors or higher, rose quite substantially.…”
Section: Davis‐bacon: Unintended Consequencessupporting
confidence: 91%
“…Almost all of the grantees and two‐thirds of the subgrantees reported that overall, Davis‐Bacon lead to wage and other cost increases (see Table ). These findings are in line with other research conducted over many years on the cost implications of Davis‐Bacon (e.g., Bilginsoy & Phillips, ; Dunn, Quigley, & Rosenthal, ; Fraundorf, Farrell, & Mason, ; Vincent & Monkkonen, ) though some studies have found to cost impacts (e.g., Duncan, ). Discussions with over a dozen subgrantees held during case study visits suggest that DoL adopted most of the wage rates that the subgrantees were already paying their in‐house staff but that wage rates for specialty jobs, such as for electricians working in multifamily buildings five floors or higher, rose quite substantially.…”
Section: Davis‐bacon: Unintended Consequencessupporting
confidence: 91%
“…The effects of prevailing wage regulations on the operations of construction labor markets and on the cost of public construction have been the subject of considerable research (Azari‐Rad, Philips, and Prus , , ; Bilginsoy and Philips ; Dunn, Quigley, and Rosenthal ; Fraundorf and Farell ; Keller and Hartman ; Vincent and Mankkonen ). However, this literature has not addressed the question of the effect of prevailing wage regulations on the participation and bidding behavior of contractors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Azari‐Rad, Philips, and Prus (, ) report relatively small and statistically insignificant prevailing wage effects, ranging between 0.025 and –1.90 percent, on the costs of building schools across the United States. However, Dunn, Quigley, and Rosenthal () point out that cost estimates based on interstate comparisons may be biased because this approach does not take into account differences in state policies and institutions that may also be related to construction costs. Vincent and Monkkonen () respond to this concern by including measures of state‐level school siting and funding laws in their interstate comparison of school construction costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Dunn, Quigley, and Rosenthal (2005) point out that cost estimates based on interstate comparisons may be biased because this approach does not take into account differences in state policies and institutions that may also be related to construction costs. Vincent and Monkkonen (2010) respond to this concern by including measures of state-level school siting and funding laws in their interstate comparison of school construction costs.…”
Section: Literature Reviewmentioning
confidence: 99%